Number 2 Feibi Recipe Inhibits H2O2-Mediated Oxidative Stress Damage of Alveolar Epithelial Cells by Regulating the Balance of Mitophagy/Apoptosis - Gu, Xiaofeng; Long, Qi; Wei, Wan; Tong, Jiahuan; Li, Zhipeng; Zhang, Zhengju; Jiao, Yang (Frontiers in Pharmacology, 2022)
ROS-mediated AEC injury and apoptosis are considered to be the initiating link of IPF, and protecting AECs can alleviate IPF. This study aimed to explore the protective effect of FBR-2 medicated serum on H2O2-mediated oxidative stress injury of AECs and further explore its mechanism. We found that FBR-2 can regulate downstream HO-1, SOD, CAT expression by activating Nrf2, reduce the level of intracellular ROS, protect mitochondrial function and improve cell survival. FBR-2 can also activate mitophagy by promoting the expression of PINK1, Parkin and LC3B-II. Moreover, FBR-2 can block the mitochondrial apoptotic mechanism and inhibit cell apoptosis by promoting the expression of anti-apoptotic proteins HK-2, XIAP and increasing the Bcl-2/Bax ratio. In summary, these data indicate that FBR-2 medicated serum can inhibit H2O2-mediated oxidative stress damage of AECs by regulating the balance of mitophagy /apoptosis. This study provides new evidence for the anti-fibrosis effect of FBR-2 and provides new drug candidates for the clinical treatment of IPF.